Dampak Latihan Resistensi terhadap Densitas Mineral Tulang pada Wanita Pascamenopause dengan Osteopenia dan Osteoporosis: Telaah Literatur - Munawwaroh, Madinatul; Sutarina, Nora (Poltekkes Kemenkes Bandung, 2026)
Background: Osteopenia and osteoporosis are common in postmenopausal women and increase fracture risk. Resistance training may positively influence bone mineral density (BMD), but optimal and safe recommendations based on FITT principles and the mechanisms underlying its effects remain uncertain. Objective: To identify effective and safe resistance training regimens for postmenopausal women with osteopenia and osteoporosis and to clarify the mechanisms underlying its effects on BMD. Methods: A systematic search was conducted in PubMed, Scopus, ScienceDirect, Cochrane, and Europe PMC up to September 2, 2025. Inclusion criteria were randomized controlled trials and quasi-experimental studies evaluating resistance training effects on BMD in postmenopausal women with osteopenia or osteoporosis, published between 2015-2025, with full-texts in English. Critical appraisal used the CEBM Oxford Critical Appraisal Tools for Therapy Study. Results: From 111 articles identified, seven met the inclusion criteria. Resistance training improved BMD through mechanical stimulation of bone formation, with site-specific and dose–response effects. Moderate to high-intensity training (60% to >80% 1-RM), targeting wrist, trunk, hip, and lower limbs, performed 2–3 times weekly for 30–60 minutes over at least six months, produced greater BMD improvements at the lumbar spine and femoral neck compared to lower intensity, with no adverse events reported. Low to moderate intensity remained beneficial, particularly with higher frequency or longer duration. Conclusion: Moderate to high-intensity resistance training is safe and most effective to increase BMD in postmenopausal women with osteopenia and osteoporosis. Professional supervision, gradual load progression, and individualized adjustments are essential to optimize outcome and ensure safety.